Self-doped Ti3+ mediated TiO2/In2O3/SWCNTs heterojunction composite under acidic/basic heat medium for boosting visible light induced H2 evolution. (21st May 2019) - Umer, Muhammad; Tahir, Muhammad; Azam, Muhammad Usman; Tahir, Beenish; Musaab, Mohammad
Abstract: Well-designed Ti 3+ /In 3+ mediated TiO2 /SWCNTs heterojunction composite for photocatalytic H2 evolution under visible light has been investigated. The samples, fabricated through one-step sol-gel approach with controlled acidic/basic heat treatment environment, were characterized by XRD, Raman, FE-SEM, TEM, XPS, UV–Vis and PL techniques. The maximum H2 of 1244 ppm h −1 was evolved over In/SWCNTs/TiO2, a 4.69, 1.54 and 1.53 times higher than using TiO2, In/TiO2 and SWCNTs/TiO2 samples, respectively. This enhancement was due to faster charges separation and higher visible light absorption by synergistic effect of In/SWCNTs. Using catalyst prepared under basic (H2 ) treatment, Ti 3+ was successfully embedded into In +3 @TiO2 @SWCNTs, exhibited H2 production of 1446 ppm h −1 which was 12.49% and 15.02% higher compared to catalysts prepared under CO2 and N2 atmospheres, respectively. Thus, surface defects like Ti 3+ inhibits charges recombination and enables visible light responsive. The quantum yield over Ti 3+ /In 3+ mediated TiO2 /SWCNTs composite was 0.251%, a 1.13 and 1.2 folds higher compared to CO2 and N2 atmospheres, respectively. Besides, excellent stability for H2 generation was observed in cyclic runs. A possible mechanism is proposed to understand synergistic effects between Ti +3 /In +3 in TiO2 /SWCNTs composite catalyst and has great potential as a green photocatalyst in environmental and energy applications. Graphical abstract: Image 1 Highlights: Ti +3 /In +3 mediated TiO2 /SWCNTs composite constructed under H2 heat treatment. H2 production over In/TiO2 /SWCNTs composite is 4.65 times higher than pure TiO2 . Using H2 atmosphere, 1.16 folds higher photoactivity for H2 achieved than N2 environment. Photoactivity enhanced with Ti +3 doping due to synergistic effect with In +3 /SWCNTs/TiO2 . Stability test revealed prolong life of catalyst in cyclic runs using visible light irradiation.